Investigating Language Style Used By Atta Halilintar in His Youtube Channel - Ratna Sari Dewi; Ririn Aulina (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
Language style can be defined as the choice of words used by a specific group of people when speak in a place and in one condition. It is necessary for people to express their thought, ideas and opinions, thus, people use style depend on with whom they speak and where they are speaking to. By understanding the language style, we also can help students in improving four English skills especially in listening and speaking. This research used qualitative descriptive method in which the data were collected from the scripts of Attas videos. The objectives of this study are (1) to describe the types of language styles that Atta Halilintar used in his video and (2) to find out the the ungrammatical sentences made by Atta Halilintar in his video. The scope of this research is a study of language variation, especially in language style found in YouTube video of Atta Halilintar. To be the data for this study taken from Attas video entitled Studio Podcast Manusia 5t Bikin Atta Kagum Sama Bang Sandy (July 5th, 2020). From this video found 965 utterances containing language styles. Then, these utterances classified and analyzed by using Martin Joos theory about language styles. The finding of this research is there are four types of language styles used in his video namely Frozen, Formal, Consultative, and Casual styles. The most common type of language styles that Atta Halilintar used is Consultative in which there are 24 utterances. He did not use intimate style since he was having a talk with Sandiaga Uno, a respected person in Indonesia. The last, the most dominant grammatical error made by Atta Halilintar was error of substitution for word usage in which there are 42 errors then followed by error of omission and the least error is addition.